أثر التكنولوجيا الرقمية على تطوير الخدمات المصرفية وتحسين القدرة التنافسية للبنوك الجزائرية - أسماء, دريد; الشيماء, نملي; نورة, عبد الجواد (University of eloued جامعة الوادي, 2020)
"الملخص: تهدف هذه الدراسة إلى تحديد دور التكنولوجيا الرقمية في تطوير الخدمات المصرفية وزيادة القدرة التنافسة ، وهذا بالاعتماد على نموذج الانحدار الخطـــي البسيط لقياس العلاقة بين المتغير المستقل و المتمثل في التكنولوجيا الرقمية ومتغيرتين تابعين يتمثلان في تطوير الخدمات المصرفية والقدرة التنافسية، ومن أجل الوصول إلى هذا الهدف تم تصميم إستبانة تتضمن المتغيرات الثلاثة وتوزيعها على عينة متكونة من 28 مشاهدة تتمثل في موظفي وكالة البنك الوطني الجزائري محل الدراسة، وذلك بالاستعانة ببرنامج (spss/25(، و يتمثل الإطار المكانـــي في وكالة الوادي، في حين قمنا بهذه الدراسة خلال شهر أفريل من سنة 2020. وتشير نتائج الانحدار البسيط للتكنولوجيا الرقمية من جهة وتطوير الخدمات المصرفية و القدرة التنافسية من جهة أخرى إلى أنه هناك دور إيجابي وفي غاية الأهمية للتكنولوجيا الرقمية على كل من تطوير الخدمات المصرفية و القدر التنافسية على حد سوا. ""Summary: This study aims to determine the role of digital technology in developing banking services and increasing competitiveness, and this is by relying on a simple linear regression model to measure the relationship between the independent variable represented in digital technology and two dependent variables represented in the development of banking services and competitiveness, and in order to reach this goal, Designing a questionnaire that includes the three variables and distributing it to a sample consisting of 28 observations represented by the employees of the Agency of the National Bank of Algeria under study, using the program (spss / 25), and the spatial framework is in the Valley Agency, while we did this study during April of 2020 . The results of the simple decline of digital technology on the one hand and the development of banking services and competitiveness on the one hand indicate that there is a positive and extremely important role for digital technology on both the development of banking services and the competitiveness of both. "
مذكرة ماستر اقتصاد نقدي وبنكي
Keywords: تكنولوجيا، رقمية، خدمات، مصرفية، تنافسية.; technology, digital, services, banking, competitive